The decision styles and level of competence of large-scale drugstore managers in Iloilo City - Pandoy, Mary Sol R.; Plameras, Mae N. (1995)
An evaluation of the decision styles and level of competence of large-scale drugstore managers in Iloilo City was conducted. The personal profile of the managers was also determined. The results showed that most managers have longer number of years rendered in one particular drugstore, only few had trainings and work experience prior to their employment in their present job, and that their highest educational attainment in the college level. The result further showed that managers have high level of competence and commonly employ evaluative decision-making style.Chi-square computations showed that there is no significant relationship between the manager's personal profile and level of competence and that the level of competence does not affect the decision styles employed. It can be said that having a longer number of service rendered to only one drugstore, the work experience and trainings and one's educational attainment do not affect one's level of of competence because, regardless of the aptitudes and experience the managers may have, their competence will not result unless the managers are not in the position to apply what have been learned. Neither does one's being highly competent may have anything to do with making decisions using perception or reasoning.
Research Paper (BA 200 - Business Research) -- Iloilo City : UPV-CM, March 1995.